ADOBE FLASH PROFFESIONAL BERBASIS MULTIPEL REPRESENTASI PADA MATERI KIMIA LARUTAN - Rizki Alfitrah; Hartatiana Hartatiana; Ravensky Y Pratiwi (Chemistry Education Department of Education and Teaching Faculty, 2021)
Chemical phenomena can be explained by three levels of representation, namely macroscopic, sub microscopic and symbolic. Chemistry learning media which includes three dimensions of representation can make it easier for students to build chemical concepts. The aim of this research is to produce a valid multipeld representation-based media on electrolyte and non electrolyte solution course, to know students respond toward multipel representation-based media on electrolyte and non electrolyte solution course that developed. This study was categorized as research and development (RnD). The media development procedure used in this research through 7 phase and adapted from Borg & Gall development model. The collecting data procedure used are interview and questionnaire. This research involve 2 material experts, chemistry teacher and expert lecturer, 1 media expert and 1 language expert. The subject of this research involve 6 students for small scale research and 30 students for medium scale research. The result of this study showed the developed media is valid and appropriate to use with detail score; 4 from experts lecturer (very good), 3.55 from chemistry teacher (very good), 3.46 from media expert (very good), 3.55 from language expert (very good), while students respond in small scale research get score percentage 90% (really agree) and students respond in medium scale research get percentage score 90.5% (really agree)